International Cooperation in The Prevention of Cybercrime - Eyyub Azizov Aydın (Scientific Trends, 2025)
This article examines the recent emergence of cybercrime as a global problem, the importance of international cooperation in society, the existing legal and operational processes, the fundamental challenges and their practical solutions. The main objection is to propose concrete measures at the legislative, practical, and policy levels in order to enhance the effectiveness of national institutions and international structures.
Keywords: Cybercrime, fraud, international cooperation, practical solutions.